COMBINATION OF SAWDUST, “FILTER CAKE” AND CALCIUM CARBONATE AS GROWTH MEDIUM FOR THE PRODUCTION OF WHITE OYSTER MUSHROOM (PLEUROTUS OSTREATUS) - & et al., Mardiana (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was aimed to investigate the effect of combining sawdust (SD), filter cake (FC) and calcium carbonate as growth medium for the production of white oyster mushroom. Isolate F2 oyster mushroom was cultured on malt extract agar (MEA) and used in the experiment. The culture medium consisted of two treatments: first, A treatment: combined medium (A0=100% SD; A1=100% FC; A2=70% FC and 30% SD; A3=50% FC and 50% SD; A4=30% FC and 70% SD) and second, K treatment: addition of calcium carbonate (K1=2%; K2=3%; K3=4%; K4=5% weight of medium). A Randomized design was used to analyze certain parameters, such as mycelial growth, presence of fruiting body, the number of fruiting bodies and the fresh weight of fruiting body at harvest. The results showed that the highest mycelial growth and fruiting body formation occurred on A0 treatment. However, a high number of fruiting bodies and a high fresh weight of fruiting body at harvest were obtained on A4 treatment. Interaction between the combined medium (A) and addition of calcium carbonate (K) showed that the highest mycelial growth occurred on A0K2 treatment 30 days after incubation. The composition of A4 treatment (30% FC and 70% SD) was found to be the optimal medium for the production of fruiting body. This finding shows that FC with additional nutrition could as a substitute of SD medium for cultivating white oyster mushroom.